Immune responses during COVID-19 breakthrough cases in vaccinated children and adolescents - Rivera-Pérez, Daniela; Méndez, Constanza; Diethelm-Varela, Benjamín; Melo-González, Felipe; Vázquez, Yaneisi; Meng, Xing; Xin, Qianqian; Fasce, Rodrigo A.; Fernández, Jorge; Mora, Judith; Ramirez, Eugenio; Acevedo, Mónica L.; et al. (Frontiers in Immunology, 2024)
Evidence of the immune response induced in the pediatric population vaccinated with CoronaVac ® , an inactivated virus against SARS-CoV-2, is limited. At the same time, the immunity induced in children and adolescents who received this vaccine and then were naturally exposed to infection with this virus and its Omicron subvariants has not been reported. This study evaluated the humoral and cellular immune responses of a pediatric population naturally infected with the virus after vaccination with two doses of CoronaVac ® using a 0-28 immunization schedule. Interestingly, we evaluated the combined response of vaccination targeting the ancestral strain and SARS-CoV-2 infection against various virus variants. This study suggests that this inactivated vaccine protected children from severe COVID-19 after SARS-CoV-2 infection. Additionally, the combination of vaccine and infection achieved high protection against the Omicron variant and its subvariants. Therefore, these results could contribute to promoting vaccination in the pediatric population and provide new evidence of the immune response in children against SARS-CoV-2 infection.